Developing high-quality human resources to meet the requirements of rapid and sustainable development: Realities and solutions - Thanh, Pham Ngoc; Tri, Nguyen Minh; Thang, Nguyen Quoc (Heritage and Sustainable Development, 2024)
The world is undergoing rapid and transformative changes, with high-quality resources playing a pivotal role in driving significant economic and social advancements. Today, the competition among nations and businesses increasingly revolves around intellectual capacity and the knowledge embedded in products, commodities, and services factors that are underpinned by superior human resources. To achieve both swift and sustainable progress, countries globally are prioritizing the development of human resources, recognizing it as a strategic and pressing necessity amidst the backdrop of global economic integration. For Vietnam, developing high-quality human resources is crucial to enhancing its competitive edge and meeting the demands of the modern digital economy. This article delves into the challenges associated with cultivating high-quality human resources needed for rapid and sustainable development. It also offers solutions to nurture these resources in Vietnam for the near future. Theoretical research is conducted from both United Nations and Vietnamese perspectives within the framework of international economic integration. This research provides both theoretical and practical foundations for advancing high-quality human resources to support sustainable development goals in Vietnam.